2000
DOI: 10.1002/1521-4028(200007)40:3<177::aid-jobm177>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of polymers degrading microorganisms in a sea-based solid waste disposal site

Abstract: In order to assess the degradability of plastics in solid waste disposal landfill sites, microbial populations capable of degrading five kinds of plastic-constituting polymers, poly epsilon-caprolactone (PCL), polylactic acid (PLA), polyethylene glycol (PEG), poly-beta-hydroxybutyrate (PHB) and cellulose acetate (CA), in a sea-based solid waste disposal site were investigated. Enumeration of aerobic and anaerobic polymers-degrading microorganisms (PDMs) was performed against to total 8 leachate samples, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…PG01, as PLA is a polyester compound known to be biodegradable. There are some reports in the literature of bacterial degradation of PLA, [12][13][14] and some of degradation by a variety of enzymes, such as lysozyme. [15][16][17] Our results show that Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…PG01, as PLA is a polyester compound known to be biodegradable. There are some reports in the literature of bacterial degradation of PLA, [12][13][14] and some of degradation by a variety of enzymes, such as lysozyme. [15][16][17] Our results show that Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…They colonize on the surface of the polyethylene films or plastic cups forming a biofilm. Cell surface hydrophobicity of these organisms was found to be an important factor in the formation of biofilm on the polythene surface, which Kathiresan and Bingham, [11] reported that bacteria caused the biodegradation ranging from 2.19 to 20.54% for polythene and 0.56 to 8.16% for plastics. Among all the species, Aspergillus glaucus was more active than A. niger in degrading 28.8% of polythene and 7.26% of plastics within a month.…”
Section: Microbial Degradation Of Polythene and Plastics In Laboratormentioning
confidence: 96%
“…the plastic materials have been colonized commonly by five species of bacteria and two species of fungi. [11] Abundance of polymer degrading microorganisms in a seabed solid waste disposal site has been reported by Ishigaka et al [12] Imam et al observed that significant biodegradation occurred only after colonization of the plastic, a parameter that was dependent on the resident microbial populations. Therefore, it can be reasonably inferred that an increase in the bacterial load has correlation with degradation of the polymer.…”
Section: Microbial Degradation Of Polythene and Plastics Under Laboramentioning
confidence: 99%
“…In recent years, there has been a renewed interest in polyesters as drug delivery devices due to their favorable biocompatibility and controllable biodegradation profiles [1][2][3][4]. Accordingly, polyester materials are regarded as a material of choice for biomedical applications including drug delivery [5][6][7][8][9], as diagnostic agents [10,11] and for tissue engineering [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%